Răspuns:
Explicație pas cu pas:
a) 14+{-7+[+4-11+(-5-4)-(-6+8-3)]+7}=14+{=7+[+4-11+(-9)-(-1)]+7}=
14+{-7+[+4-11-9+1]+7}=14+{-7+[-15]+7}=14+{-7-15+7}=14+(-15}=14-15=-1
b) [(3-2+1)-(-5-4+7)-(+4)]-[7+(-3-2+4)-(-4+3+1)+(-6)]=
[2-(-2)-4]-[7+(-1)-0-6]=[2+2-4]-[7-1-6]=[4-4]-[7-7]=0-0=0
c) -5-{-1+[-3+(-5-2)]-[-4-(-7-4)+(-3+7)]-2}=-5-{-1+[-3+(-7)]-[-4-(-11)+4]-2}=
-5-{-1+[-3-7]-[-4+11+4]-2}=-5-{-1-10-11-2}=-5-(-24)=-5+24=19
d) 4+{1-[2-(-5-1)+(-3+2)]-[-2+(2-5)-(-3+5)]-4}=
4+{1-[2-(-6)+(-1)]-[-2+(-3)-2]-4}=4+{1-[2+6-1]-[-2-3-2]-4}=4+{1-7-(-7)-4}=
4+{1-7+7-4}=4+{-3}=4-3=1